An Intramolecular Charge Transfer Induced Fluorescent Chemosensor for Selective Detection of Mercury (II) and its Self‐Turn‐On Inside Live Cells at Physiological pH. Issue 17 (3rd April 2019) - Kumar, Alok; Ananthakrishnan, Rajakumar; Jana, Gourhari; Chattaraj, Pratim K.; Nayak, Santoshi; Ghosh, Sudip K.
Abstract: A new turn‐on fluorescence small‐molecular dicarboxylic acid functionalized chemosensor (L2) has been designed strategically. The bidentate ligand (L2) is exceedingly selective for the sensing of Hg II ions over other heavy‐metal ions, and exhibits excellent resolution on imaging living cells in‐vitro . The Hg II binding mechanism by the probe occurs selectively through lone pair of electrons from imine nitrogens, which was established by using 1 H NMR titrations, density functional theory (DFT) and time‐dependent density functional theory (TD‐DFT). The free acid protons facilitated enhanced fluorescence intensity upon shift at deprotonation and gave a 50 nm hypsochromic at slight basic medium. The para‐ and meta‐positions of imine nitrogen atoms with respect to the donor (NH2 ) inducing the intramolecular charge transfer (ICT). The designed probe has high sensitivity to mercury(II) ions, excellent cell membrane permeability and negligible cytotoxicity, which result in bright and specific detection of Hg II in living cells (HeLa cells) by fluorescence turn‐on at physiological pH. Further, the strategic approach executed in this work would be useful to design new chemosensors for sensing of different molecules or ions in future. Abstract : At physiological pH ligand (L2) gives the enhanced fluorescence in presence of mercury (II). This effect has been utilized in‐vitro imaging application for detections of mercury (II) without any co‐reagent to turn‐on fluorescence via ICT mechanism.